2015
DOI: 10.1038/ejcn.2015.87
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of protected mealtimes are associated with improved mealtime energy and protein intakes in hospitalized adult patients on medical and surgical wards over 2 years

Abstract: Aspects of protected mealtimes were associated with improved intake. Identifying these achievable aspects during planning and ensuring successful implementation of protected mealtimes may be critical for optimizing acute inpatient intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 18 publications
0
30
0
3
Order By: Relevance
“…Although the KA scores were relatively high for this group, the P scores demonstrate room for improvement. For example, proponents of “protected mealtimes” suggest decreasing mealtime interruptions [27,28,29,30], yet only 35% of M2E hospital staff arrange their tasks to minimize this interruption. Food intake is an important factor for determining length of stay, and 82% agreed/strongly agreed that monitoring food intake was important, yet this was not always done in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Although the KA scores were relatively high for this group, the P scores demonstrate room for improvement. For example, proponents of “protected mealtimes” suggest decreasing mealtime interruptions [27,28,29,30], yet only 35% of M2E hospital staff arrange their tasks to minimize this interruption. Food intake is an important factor for determining length of stay, and 82% agreed/strongly agreed that monitoring food intake was important, yet this was not always done in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, many studies have examined the prevalence of malnutrition [15], the barriers to food intake [68], and ways to protect mealtimes [912] in hospital. Few studies have attempted to describe how to improve hospital nutrition care practices and embed those practices in the unit routine [13].…”
Section: Introductionmentioning
confidence: 99%
“…This has been in recognition of the ageing and frail hospital population (Bagshaw et al, 2014;Joosten, Demuynck, Detroyer, & Milisen, 2014), known challenges associated with opening food and beverage packaging and self-feeding in hospital (Bell et al, 2013;Tsang, 2008), and staffs' limited time and resources (Eide, Halvorsen, & Almendingen, 2015;Ross, Mudge, Young, & Banks, 2011). Studies have shown that 31%-52.5% of patients need assistance at mealtimes (Palmer & Huxtable, 2015;Westergren, Karlsson, Andersson, Ohlsson, & Hallberg, 2001;Young et al, 2016). Mealtime assistance programmes aim to improve patients' access to and consumption of meals in hospital by enlisting trained or untrained staff, volunteers and visitors to help patients at mealtimes.…”
Section: Introductionmentioning
confidence: 99%